Impactos da inserção da criança com deficiência no ensino regular - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The trajectory of Brazilian education as a social policy has its visibility in the struggles of society for access, quality and permanence, based on the guiding principles of citizenship that historically includes the "different". The present Work of Conclusion of Course in Social Work has as its objective to problematize the impacts experienced by the disabled child when entering the regular education. The study consists of a bibliographical and documentary research, based on the documents elaborated in the process of Supervised Internship in Social Work aiming to highlight the particularities apprehended during internships I and II. It should be noted that among the main impacts of the inclusion of children with disabilities in regular education are the lack of trained professionals to assist students with disabilities, the structure of schools, exclusion processes that involve (non) acceptance of the public in general, even if access to education is a right for all, a quality education, regardless of the student being disable or not. Based on this scenario, the analysis of information, by way of conclusion, points to the importance of the triad: school, family and child, as necessary in the inclusion process, with a greater emphasis on family and community participation so that the inclusion is indeed a concrete reality.
Keywords: Educação; Educação especial; Inclusão escolar; Ensino; Crianças deficientes; Família; Children with Disabilities; Education; CNPQ::CIENCIAS SOCIAIS APLICADAS